Aplikasi Administrasi Kependudukan RT Berbasis Website Dengan Pengembangan Model Waterfall - Bambang Santoso (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Rukun Tetangga (RT) is a Community Institution under the Rukun Warga and Kelurahan or Village. As the smallest community institution, the RT assists the Lurah or Village Head in the field of government services, and provides population data and permits. These tasks should be carried out quickly, precisely, accurately, accompanied by a complete report at the end of the month or the end of the quarter. For this, information technology can significantly assist the RT's tasks by making data on residents and families neatly and structured in a database. A request for a letter can be made without the residents having to meet with the administrator. This is very helpful especially because the RT management is still actively working so time is limited. The system development method uses a systematic Waterfall model. Application is web-based, using PHP programming language. The database uses MySQL and the web server is Apache; both are bundled in XAMPP package. The result of the research is a RT population administration program that can assist the activities and tasks of RT administrators.